The Islamic Legal Construction on Global Peace: An Integrative Study of Maqāṣid al-Syarī'ah and the United Nations Charter - Razi, Fahrur; Ananda Prayogi (Tribakti: Jurnal Pemikiran Keislaman, 2026)
In a world that is constantly being shaped by armed conflicts and geopolitical instability, there is an increasingly urgent need for a legal framework that can support global peace. The United Nations (UN) Charter has long formed the basis of international law, promoting peace and preventing aggression. However, its effectiveness is often hindered by various structural limitations, such as power imbalances and weak enforcement of sanctions. Against this backdrop, maqāṣid al-syarī‘ah, the core of Islamic legal theory, can make a significant contribution as both an ethical-religious instrument for Muslims and a universal paradigm to reinforce the spirit and structure of the UN Charter. This article aims to construct an Islamic legal framework for global peace by taking an integrative approach to maqāṣid al-syarī‘ah and the principles of international law set out in the UN Charter. It will be compared with classical and contemporary fiqh siyasah. A normative-comparative methodology is employed, analysing primary sources such as the works of Ali Haidar and Yusuf al-Qaradawi, alongside case studies of global conflicts in various regions, including Palestine–Israel, Syria, Ukraine, and Yemen. The results of the study show that maqāṣid al-sharīʿah, with its core values of hifẓ al-nafs (protection of life), al-ʿadl (justice), and al-silm (peace), aligns with the principles of the UN Charter and can provide an ethical and spiritual dimension largely absent from modern international law. Unlike fiqh siyasah, the UN Charter prioritizes formal legality, whereas Islamic law emphasizes moral legitimacy and substantive justice. The article concludes that integrating maqāṣid al-syarī‘ah into global peace law discourse could enrich global civilisation with a more humane, inclusive and transnational approach.